2018
DOI: 10.1038/s41398-018-0312-6
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal asymmetries in subcortical brain volume in early adolescents with subclinical psychotic experiences

Abstract: Subcortical structures may have an important role in the pathophysiology of psychosis. Our recent mega-analysis of structural magnetic resonance imaging (MRI) data has reported subcortical volumetric and lateralization alterations in chronic schizophrenia, including leftward asymmetric increases in pallidal volume. The question remains, however, whether these characteristics may represent vulnerability to the development of psychosis or whether they are epiphenomena caused by exposure to medication or illness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 63 publications
4
20
1
Order By: Relevance
“…Enlarged volume of left-lateral ventricle found in adolescents with HDS are concordant with large scale studies of schizophrenia (Naohiro Okada et al, 2018;van Erp et al, 2016), FEP (Ellison-Wright et al, 2008) patients, as well as in adolescents with SPEs (Naohiro Okada et al, 2018). However, in FEP patients, some contradiction exist, as longitudinal studies have showed a progressive enlargement occurring after the first episode and especially within the first years of illness (Kempton et al, 2010).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Enlarged volume of left-lateral ventricle found in adolescents with HDS are concordant with large scale studies of schizophrenia (Naohiro Okada et al, 2018;van Erp et al, 2016), FEP (Ellison-Wright et al, 2008) patients, as well as in adolescents with SPEs (Naohiro Okada et al, 2018). However, in FEP patients, some contradiction exist, as longitudinal studies have showed a progressive enlargement occurring after the first episode and especially within the first years of illness (Kempton et al, 2010).…”
Section: Discussionsupporting
confidence: 82%
“…To date, studies investigating psychometric schizotypy have employed cross-sectional designs with success in identifying cerebral alterations linked to the expression of schizotypy (Kühn et al, 2012a;Naohiro Okada et al, 2018), but their ability to provide information about developmental trajectories is limited. The present study investigates dynamic changes in subcortical structure development in relation to the three dimensions of schizotypy (positive, negative and disorganized).…”
Section: Introductionmentioning
confidence: 99%
“…Smaller caudate volume has previously been reported in first episode psychosis 64 , with further decreases as psychotic symptoms worsen 65 . There are also studies reporting larger volumes of striatal structures in schizophrenia 66 but these tend to be linked to antipsychotic drug exposure. A larger accumbens has been linked resilience to subclinical symptoms 67 , while decreased volume of the putamen has been associated with AVHs in the context of schizophrenia 68 .…”
Section: Gray Mattermentioning
confidence: 99%
“…Asymmetries in brain organization are often considered at an average level across a population of individuals (7,10,(13)(14)(15). Also called directional asymmetries (12,16), they have been studied extensively and are thought to have important implications for both functional lateralization and abnormal brain function in a wide range of psychiatric and neurological diseases (5,11,15,(17)(18)(19)(20)(21)(22)(23)(24)(25). However, the specific regions showing these asymmetries, their directions, and their magnitudes are often inconsistent (10,11,13).…”
Section: Introductionmentioning
confidence: 99%